Political economy of millennium development goals: a critical assessment of achievement and strategies - Md. , Moniruzzaman (2014)

(untitled)
The Millennium Development Goals (MDGs) are a noble initiative to deal with certain chronic socioeconomic problems of the backward societies. Targeted to achieve eight major goals by 2015, the initiative deserves critical assessment of its achievement and strategies as its time frame is approaching to an end. Based on data on the goals achievement from the relevant countries, this article argues that while significant achievements are noticeable, these are far less than satisfactory in real terms, secondly, nonachievement of the goals are due to three large factors; first, uncertain international political economic structure and market functioning; second, international power-politics which intentionally affect regime sustainability in the countries concerned; and third, domestic dynamics of political power-play which influences allocation of resources for short-term political gains. The research makes a cross-country comparative analysis adopting an approach of institutional analysis in comparative politics.